The Influence of Product Innovation, Operational Efficiency and Brand Reputation on Sales Increase Strategy - Puspajati, Izzatillah; Ali, Hapzi (Siber Journal of Transportation and Logistics, 2024)
This article is a literature study in the field of strategic management. It discusses the influence of product innovation, operational efficiency, and brand reputation on sales improvement strategies. The hypothesis of the influence between variables will be used in future research. Online libraries, Google Scholar, Mendeley, and other academic media use research objects. The research method that uses library browsing comes from e-books and e-journals that are publicly accessible. Descriptive qualitative analysis The results of this article are as follows: Product innovation influences sales increase strategies; operational efficiency affects sales improvement strategies; and brand reputation influences sales improvement strategies.